En. Shaharom TM Sulaiman / Akilah Nadirah Roszelin, Shantie Mohamad and Mohamad Hafiz Abdullah - Roszelin, Akilah Nadirah; Mohamad, Shantie; Abdullah, Mohamad Hafiz (2014)
En. Shaharom TM Sulaiman merupakan seorang pengarang Malaysia yang berasal dari Pekan, Pahanq. Dilahirkan pada 23 April 1962.